Mito Desmascarado: o super-herói Americano em Ex Machina - Pinheiro, Victor Souza (2016)
The terrorist attack that hit the World Trade Center in New York on September 11, 2001, caused a historical impact in the United States of America, awakening in the country’s cultural industry a massive, patriotic reaction of endorsement of the War on Terror that followed. One of the centerpieces of that period, the American Superhero, however, was also mobilized to articulate criticism to the George W. Bush’s military campaign in some comics of the time, which also problematized the condition of that mythical figure of mass culture, a recognized nationalist symbol, during an increasingly contested government – by both the domestic population and the global community. This study aims to present the Ex Machina series, by Brian K. Vaughan and Tony Harris, as a radical example of this production, invoking the methodological support of Discourse Analysis to reveal the corrupt protagonist Mitchell Hundred (or The Great Machine ) – elected mayor of New York City after saving one of the Twin Towers on a reimagined September 11 – not only as a critical reflection of the Bush administration, but a demythifying appropriation of the American Superhero, one that invests itself with a critical view of the constitutive ideology of the superheroic paradigm and shows it as a reproduction of the redemptive and benevolent facade under which the USA imposes its international authority, in alleged missions for world peace, while obscure abuses and controversial geopolitical ambitions.